KONSTRUKSI PERLINDUNGAN HUKUM TERHADAP KEBEBASAN PERS DALAM IUS CONSTITUENDUM INDONESIA - Rahel Octora (Arena Hukum, 2018)
AbstractIn order to conform the law with the societyâ€™s development, the Goverment is drafting the bill of Indonesian Criminal Code as well as the bill concerning Broadcasting. The problem that arise in the drafting process of the two bills as ius constituendum is the criminalization of anyone who violates the law: publishes anything that may affect the imparciallity of the judges in the contempt of court trial and the rules in the Broadcasting bill concerning the prohibition of exclusive screening of investigative journalism. This article is compiled using a normative juridical method, which refers to a research method by analyzing data and linking it to the applicable legal rules. The results of the study show that in order to guarantee press freedom and provide balanced protection for the interests of society, the act of publishing news that can influence the impartiality of judges should be considered as an ethical violation and not a violation of criminal law. As for the regulation of the prohibition of exclusive screening of investigative journalism in the Broadcasting Bill, an explanation needs to be given so that it does not cause multiple interpretations, and does not conflict with the principle of diversity of content.Â AbstrakPemerintah sedang menyusun Rancangan Kitab Undang-undang Hukum Pidana (RKUHP) dan Rancangan Undang-undang Penyiaran. Adapun permasalahan yang muncul dalam proses perancangan kedua RUU tersebut sebagai Ius Constituendum di Indonesia adalah adanya kriminalisasi terhadap setiap orang yang secara melawan hukum: mempublikasikan segala sesuatu yang menimbulkan akibat yang dapat mempengaruhi sifat tidak memihak hakim dalam sidang pengadilan (delik contempt of court) di dalam RKUHP dan adanya aturan di dalam RUU Penyiaran tentang pelarangan penayangan eksklusif jurnalisme investigasi. Artikel ini disusun menggunakan metode yuridis normatif, yang mengacu pada suatu metode penelitian dengan menganalisis data dan mengkaitkannya dengan aturan hukum yang berlaku. Hasil penelitian menunjukkan bahwa untuk dapat menjamin kebebasan pers dan memberikan perlindungan berimbang bagi kepentingan masyarakat, tindakan mempublikasikan berita yang dapat mempengaruhi imparsialitas hakim seharusnya dianggap sebagai suatu pelanggaran etika dan tidak perlu dikriminalisasi. Sedangkan untuk pengaturan pelarangan penayangan eksklusif jurnalisme investigasi di dalam RUU Penyiaran, perlu diberikan penjelasan agar tidak menimbulkan multitafsir, dan tidak bertentangan dengan prinsip diversity of content.